Curricular reforms in the transformation of nursing teaching in a federal university - Stéfany Petry; Maria Itayra Padilha; Roberta Costa; Joel Rolim Mancia (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to discuss the curricular reforms adopted for nursing teaching in Brazil, from 1969 to 2019. Methods: historical, qualitative approach using the thematic oral history and document research. 13 interviews were carried out with graduation nursing professors from a federal university in the South of Brazil. The document sources were the political-pedagogical projects of the course and their associated documents. Minayo's thematic analysis was used. Results: nursing curricula delineates the profile of the professional that must be formed and are reviewed in order to be adapted to social and educational changes, showing the scientific and professional potential of the nurse. Curricular reforms consider the quality of nursing formation. Final Considerations: the structure of the curriculum and the reforms that took place emerged according to the historical, political, epidemiological and social context demanded from the profession, to attend to the demands of society and to the work market.